Role of fine needle aspiration cytology in diagnosing leprosy: in a tertiary care hospital - Nandwani, Radhika Rajesh; Totade, S. K.; Gupta, Usha; Jain, Mukesh (International Journal of Research in Medical Sciences, 2017)
Background: Leprosy, a chronic inflammatory granulomatous disease chiefly involving skin and peripheral nerves and occasionally other organ systems, caused by Mycobacterium leprae. It has tormented the human civilization through time immemorial. Leprosy remains a significant public health problem worldwide, especially in developing countries like India. The diagnosis of leprosy is not always easy because of long incubation period, over dependence of clinical expertise and a lack of rapid and simple diagnostic tool, patients remain undiagnosed for longer time. Fine needle aspiration (FNAC) technique is an inexpensive, rapid and accurate procedure for diagnosis of leprosy. We conducted a prospective study evaluating the ability of fine needle aspiration cytology in diagnosing and classifying leprosy lesions on Ridley-Jopling scale (R-J scale). The aim of this prospective study was to assess the usefulness of fine needle aspiration cytology in early diagnosis of leprosy, to identify specific cytological characteristics of diagnosis and to correlate the cytological smear findings with histopathology and to evaluate merits of relatively non-invasive procedure of FNAC over more invasive procedure - biopsy. Methods: The study is a hospital based prospective study carried out in the Department of Pathology and Department of Skin, Venereal Diseases, Leprosy, N.S.C.B. Medical College & Hospital, Jabalpur (M.P.) September 2010 to September 2013. Patients with new skin lesions were selected for the study. FNAC was performed and aspirates were evaluated for cytology using Hematoxylin and Eosin staining (H&E staining), Ziehl-Neelsen staining (ZN staining) and punch biopsy was collected. Results: Out of 50 cases, clinical and cytological correlation was seen in 88% tuberculoid leprosy, 93.7% of borderline tuberculoid, 33% of borderline lepromatous leprosy and 66% of lepromatous leprosy. While clinical with histopathological correlation revealed 100% specificity in tuberculoid leprosy, 100% in borderline tuberculoid, 66.6% in borderline lepromatous, 83.3% in lepromatous leprosy and 80% in indeterminate leprosy and 100% in histoid leprosy in our study. The overall cytodiagnostic accuracy has been 92% in present study. Conclusion: Our study demonstrates that the combination of FNAC and ZN staining for Acid Fast Bacilli (AFB) can provide a rapid diagnosis in majority of leprosy suspected cases. FNAC is a safe, simple, rapid, less-invasive, OPD procedure for early diagnosis and classification of leprosy cases.